Network Analysis on Information Seeking regarding the Gaza Humanitarian Movement among Communication Students of the Catholic University of Widya Mandira Kupang - Pratama, Imam Agi; Ridlo, Muhammad Rosyid; Setyaningsih, Fransiska Desiana; Heri, Edwar Andiko (Green Publisher Indonesia, 2025)
This study examines the communication network among Communication Science students at Widya Mandira Catholic University (Unwira) Kupang regarding information-seeking behaviors related to the Gaza humanitarian movement. Information is a critical human need, and understanding how students access and disseminate such information highlights the role of social networks in collective action. The research aims to analyze network patterns, identify key actors, and assess the efficiency of information flow within the student network. Using a quantitative approach with Social Network Analysis (SNA), data were collected via online questionnaires from 67 respondents, focusing on direct and reverse information-seeking, expertise recognition, and friendship ties. UCINET and NETDRAW software were employed to visualize and analyze network structures. Findings revealed a sparse network density (1.35%–1.54%), indicating fragmented communication channels. Key actors, such as Actor #61, emerged as central figures due to their expertise and active roles in information dissemination. Despite low overall density, these actors facilitated information flow, particularly within smaller subgroups. The study underscores the importance of social networks in humanitarian movements and suggests practical strategies for enhancing communication efficiency among students. Academic implications include advancing SNA theory, while practical recommendations focus on leveraging key actors to improve information dissemination in social movements.